2019
DOI: 10.1093/ageing/afz031
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in rehabilitation interventions after hip fracture: a systematic review

Abstract: Objective to determine the extent to which equity factors contributed to eligibility criteria of trials of rehabilitation interventions after hip fracture. We define equity factors as those that stratify healthcare opportunities and outcomes. Design systematic search of MEDLINE, Embase, CINHAL, PEDro, Open Grey, BASE and ClinicalTrials.gov for randomised controlled trials of rehabilitation interventions after hip fracture pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 20 publications
0
25
0
3
Order By: Relevance
“…3 Despite dementia being common among older people with hip fracture and that the population has complex care needs, 6 the condition has often been an exclusion criterion for participation in previous clinical trials. 8 There is, however, growing evidence that people with hip fracture and cognitive impairment (CI) or dementia benefit from enhanced interdisciplinary rehabilitation in hospital, 9,10 combined in-hospital and in-home rehabilitation, [11][12][13][14] and from rehabilitation in nursing homes, 15 although the optimal rehabilitation strategies remain unclear. 6 To our knowledge, no previous team-based home rehabilitation (HR) interventions after hip fracture have included people with severe CI or dementia.…”
Section: Introductionmentioning
confidence: 99%
“…3 Despite dementia being common among older people with hip fracture and that the population has complex care needs, 6 the condition has often been an exclusion criterion for participation in previous clinical trials. 8 There is, however, growing evidence that people with hip fracture and cognitive impairment (CI) or dementia benefit from enhanced interdisciplinary rehabilitation in hospital, 9,10 combined in-hospital and in-home rehabilitation, [11][12][13][14] and from rehabilitation in nursing homes, 15 although the optimal rehabilitation strategies remain unclear. 6 To our knowledge, no previous team-based home rehabilitation (HR) interventions after hip fracture have included people with severe CI or dementia.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing focus on using an equity lens to critically review the development and evaluation of health (and other) interventions for populations who may experience health inequities to ensure that the evidence generated is of relevance for both clinical practice and public policy making [57]. The lack of equity in trials of interventions, such as rehabilitation interventions after hip fracture, for adults who lack capacity has been identified as a result of their exclusion from trials [19] based on equity factors (e.g. PROGRESS+ factors [57]).…”
Section: Methodological Challengesmentioning
confidence: 99%
“…A recent review of studies on the NIHR portfolio found that 60% of the studies excluded learning disability groups, none of the studies investigating pneumonia or sepsis included learning disability groups despite being a key contributor to premature deaths, and only 1.4% of all studies were specifically related to learning disabilities [18]. Similar exclusions of people with cognitive impairment are seen in other areas of research such as geriatrics [7], rehabilitation interventions following hip fracture [19], perioperative medicine [20], trauma [21] and neurological research [22]. Under-recruitment to research into conditions such as dementia is one of the key challenges to advancing understanding of these conditions and improving the care and treatment of those who live with these conditions [23].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…People living in nursing care facilities (NCFs) are often excluded from participating in research and clinical trials [1] which has contributed to a lack of information regarding the usual clinical care provided in NCFs to residents following their return from hospital after hip fracture surgery. This lack of information makes the development of practice guidelines difficult.…”
Section: Introductionmentioning
confidence: 99%